Material modification of 3D objects on the web - Dušek, Václav; Svoboda, Jaroslav; Dušek, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The main goal of this thesis was to solve the visible texture repetition in 3D graphics on the web. For the rendering of the 3D scene is used WebGL as the main technology for 3D graphics on the web. The WebGL is handled with the help of the Three.js framework. The texture repetition is solved by the implementation of several techniques. These techniques are distance tiling and micro and macro variation. The texture bombing was not implemented because it is not suitable for some types of textures. The material, that will not have noticeable texture repetition, was created by inheriting properties from MeshStandardMaterial, which comes with Three.js. The mentioned techniques were implemented with the use of GLSL as a part of vertex shader and fragment shader. These parts of GLSL codes were injected into the original GLSL code that was inherited from MeshStandardMaterial. The last step was to add new properties to the material to be able to control variables in the GLSL code. This results in material, that hides the texture repetition by adding more visual variation to the final look.
Vedoucí práce: Jaroslav Svoboda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses